PREVENTION OF HYPOVITAMINOSIS IN SCHOOL CHILDREN - O.A. Gromova (Union of pediatricians of Russia, 2009)
The author focuses on the causes of vitamin deficiency in this article dedicated to the issues of hypovitaminosis in the children population. It also describes the consequences of a vitamin and mineral deficiency in the body. Given the interaction of individual vitamins and minerals, the author demonstrates the best efficacy of complex medications. In addition, the article stresses the need for a preventive administration of these medications ensuring the normal level of minerals and vitamins, and, hence, an optimal functioning of a child's body organs and systems.Key words: vitamins, minerals, deficiency, correction ways, children.